Oil spill cleanup techniques in the marine environment - Zahed, M.A.; Aziz, H.A.; Isa, M.H. (2006)
Large amounts of hydrocarbons are extracted, produced, refined and handled on land every year. Despite improvements in careful handling, transportation and containment, there is still the possibility that some may enter the environment. The accidental release of oil has been shown to cause serious damage to natural ecosystems when improperly managed. The catastrophic oil spill accidents have been occurred to marine environments and several methods have been suggested for petroleum clean up in aquatic ecosystems. This article briefly reviews the most recent development and advances of physical, chemical and biological techniques as well as data interpretation which are most frequently used in oil spill clean up studies, including dispersants, demulsifiers, cleaners, booming, low pressure flushing, bioremediation and several other emerging techniques. The issue of how bioremediation are employed for cleaning sea waters is also addressed.